Epidemiology and genetic characterization of human sapovirus among hospitalized acute diarrhea patients in Bangladesh, 2012–2015. Issue 11 (10th June 2021) - Rahman, Rajibur; Rahman, Sezanur; Afrad, Md M. H.; Talha, Muhammad; Islam, Deen; Uddin, K. M. Main; Ahmed, Shahnawaz; Afrad, Mokibul H.; Faruque, Abu S. G.; Hossian, Mohammad E.; Rahman, Mustafizur
Abstract: Human sapovirus, which causes acute gastroenteritis, is not well studied and poorly understood. This study aims to investigate the contribution of sapovirus in diarrhea, their clinical association, and genotypic diversity. Fecal specimens ( n = 871) were randomly selected from diarrheal patients who attended International Centre for Diarrhoeal Disease Research, Bangladesh hospital in Dhaka, Bangladesh during January 2012–December 2015 and tested for the presence of sapovirus RNA using real‐time polymerase chain reaction. Sapovirus RNA was identified in 2.3% ( n = 20) of the samples. Seventy‐five percent of the sapovirus positive cases were coinfected with other pathogens, such as rotavirus, norovirus, enterotoxigenic Escherichia coli, adenovirus, Shigella spp ., and Vibrio cholerae . A vast genetic diversity was observed among sapovirus with at least seven common genotypes (GI.1, GI.2, GI.7, GII.1, GII.4, GII.6, and GIV), and a new genotype GII.NA1. Some of the GI.1 strains detected were similar to GI.4 in the polymerase region sequence and were confirmed as recombinant strains. Our findings suggest that the overall contribution of sapovirus in hospitalized diarrheal illness is low but highlight enormous genetic diversity. Highlights: The findings of this study provide a new insight into the extent of co‐infections and genetic diversity of sapovirus.